Pengembangan E-Learning Berbasis Chatbot AI untuk Pembelajaran IPA Inklusif di SD Lahat - Selvia Damayanti; Selvy megira (BETRIK, 2025)
The advancement of Artificial Intelligence (AI) has significantly influenced various fields, including education. In the digital era, integrating technology into education has become indispensable, particularly in fostering inclusive and adaptive learning systems. The urgency of this study arises from challenges in elementary-level Science (IPA) learning, where students frequently struggle to comprehend material outside school hours. Limited instructional time, disparities in students’ understanding, and the scarcity of interactive media remain key obstacles in the learning process. To address these issues, this research proposes the development of an AI-based chatbot integrated into an e-learning platform as an innovative solution to support Science learning in elementary schools within Lahat Regency. The chatbot is designed to function as a virtual learning assistant, capable of providing real-time responses, delivering adaptive explanations, and enhancing student engagement through personalized interaction. This study adopts a Research and Development (R&D) methodology, employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Each development phase involves both students and teachers to ensure alignment with learning needs and to evaluate the effectiveness of the chatbot in the Science learning context. The expected outcome of this research is the establishment of an AI-based chatbot learning medium that enhances students’ comprehension, facilitates independent learning, and offers an alternative strategy to mitigate teachers’ limitations in Science instruction. Ultimately, this study contributes to advancing inclusive, interactive, and adaptive innovations in elementary education within the digital era.